The Application of Presentation Practice Production Method for Teaching Speaking Skill: The Perception of Teachers and Students - Mas Darul Ihsan (Universitas Kanjuruhan Malang, 2020)
The research is to know the application of teaching English by Using â€œPresentation Practice Productionâ€ method and its effect on teachers and students in MI Masyhudiyah, Gresik, East Java. Qualitative research was used by combining questionnaire, interview and secondary data, teachersâ€™ lesson plan of all English Teachers. The theory was based on (Larsen, 2003), (Jordan, Carlile, & Stack, 2008) and (Brown, 2000). The finding and discussion were, first, the application on teachers created: 1) the students tent to be more having bravery to do such a conversation in English, getting more focus and stable to have talks among. 2) The students got easily imitate and follow the English lesson by what the teacher taught in the classroom. Second, the effects on teachers were 1) teachers got the easiness in conveying the teaching materials in the classroom, improving the speaking skill, and getting more focus on teaching materials. 2) Teachers could see directly the results from the teaching at the day. The last, the effect on students are 1) Students could directly use the words, utterances and conversation at the day and more active, more focus and more perceptive in studying English. 2) The students were impressed by using English fingers.